Odpowiedzi

2009-11-11T11:00:42+01:00
A) a1 = -2, q = 0,5

b) a1 = 3, q = - ⅓

c) a1 = - 1,5; q = 2


a) a₅=a₁×q⁴=-2×(½)⁴=-2×1÷16=-⅛
b)a₅=3×(-⅓)⁴=3×(-1/81)=-1/27
c)a₅=-1,5×2⁴=-24
Najlepsza Odpowiedź!
2009-11-11T11:03:05+01:00
A)

a1=-2 q=1/2

a2=a1*q
a2= -2* 1/2=-1

a3=a2*q= -1*1/2=-1/2
a4=a3*q=-1/2*1/2=-1/4
a5=a4*q= -1/4*1/2=-1/8

b)a1=3 q=-1/3
a2=a1*q=3* -1/3=-1
a3=a2*q=-1*-1/3= 1/3
a4=a3*q=1/3* *-1/3=-1/9
a5=a4*q=-1/9* -1/3=1/27

c)a1=-3/2 q=2
a2=-3/2*2= -3
a3=a2*q=-3*2=-6
a4= -6*2=-12
a5=-12*2=-24